CORRELATION BETWEEN READING HABIT AND WRITING SKILL OF THE EIGHTH GRADERS AT SMP NEGERI 6 KAYUAGUNG - Riska Yohana; Dewi Sartika; Rekha Asmara (Universitas Islam Ogan Komering Ilir Kayuagung, 2021)
Many researches have shown the facts that the students’ skills in writing can be improved by having a good reading habit. It was convinced that the students reading habit has great impact on the improvement of students’ writing ability. The students who read extensively will acquire more vocabularies that lead them to have greater proficiency in writing. Therefore, this study was purposed to know whether reading habit of the eighth graders of SMPN 6 Kayuagung was significantly correlated to their writing skill. By means of Purposive sampling, 124 students of the whole number of the population were selected as the sample. A correlational study was applied. A questionnaire and written test were distributed to get the data. Twenty items of a ready-made questionnaire were used to know students’ habit in reading and a writing test was a dmin ist er ed to measur e students’ writing skill. The writing test was reliable because its reliability coefficient was 0.942. In data analysis, Pearson Product Moment Correlation coefficient on SPSS 20 was used. The findings revealed that r-obtained (0.685) was bigger than the value of r-table (0.176) at p-value which was less than 0.05. Thus, the formulated hypotheses were proved. In other words, there was a significant correlation between reading habit and writing skill of the eighth graders at SMPN 6 Kayuagung